Students’ Perceptions of the impacts of Short Diplomatic Course 2023: An Interpretive Phenomenology on Diplomatic Academic Experience, Personal Development and Global Perspective - Juliana, Juliana (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
Purpose of this research was to examine students’ perception of international relation on the impact of short diplomatic course program 2023 with the topic "countries efforts in combating global warming” as part of diplomatic course that offers essential training, knowledge, and skills for students. The participants were international relation students of Potensi Utama University. Research design used interpretative phenomenological analysis. Data collection was conducted using semi-structured interviews to explore informants' views on their experiences to derive key themes from their experiences related to this research. The research analysis resulted in three main themes: academic materials and experience, personal development and global perspective. Some of the themes show that the impact of short diplomatic course program 2023 is multifaceted. The educational topics of the program substantially focused on the global issues of “countries efforts in combating global warming”. The research also relied heavily on students' self-reported answers. Findings can be used as a conceptual tool for the design and evaluation of new and existing programmes. In addition, the three main themes that emerged from this research are useful as prompts for students' self-reflection on their own academic experiences and personal development. In short, the students enjoyed learning and participating in short diplomatic course which automatically improved their diplomacy academic experience, personal development, global perspective.